Quand l’inclusion inversée tend à bousculer la forme scolaire en école maternelle - Amael André; Diane Bedoin (Recherches en Éducation)
Since 2014, Autism Kindergarten Education Units (UEMA) were set up. Combining specialized and ordinary environments, they aim to meet the specific needs of children with Autism Spectrum Disorders (ASD). This study aims at identifying the obstacles and facilitators related to the inclusion of young children with ASD attending school in UEMA. The analysis focuses more specifically on the reverse inclusion system, with an activity shared between children in ordinary classes and those with disabilities within the specialized unit, which contrasts with the inclusion usually implemented and which tends to disrupt the traditional school form. From a double theoretical framework — in social psychology and in interactionist sociology — and a mixed methodology — filmed observations and semi-structured interviews — the case study allows to identify how reverse inclusion structure affects the way of thinking and organizing the school form, by playing on the dynamics of interactions between young children with ASD (in terms of social participation) and adults (in terms of guidance).